How can derivatives contribute to sustainable development goals? An analysis of synergies, contradictions, and challenges - Maria-Teresa Bosch-Badia; Joan Montllor-Serrats; Maria-Antonia Tarrazon-Rodon (Sustainable Futures)
This paper examines the derivatives' actual and potential effects on the Sustainable Development Goals (SDGs) progress. It explores how derivatives affect the SDGs from a conceptual standpoint, identifying both synergies and contradictions. One significant synergy is the alignment of derivatives supply with the financial risks associated with the SDGs, supported by the regulatory framework that helps control volatility peaks. However, a major contradiction exists in the risk management gap between developed and developing economies. Two actions to narrow this gap arise from the analysis undertaken in this paper: first, strengthening financial literacy by including risk management and basic knowledge on derivatives and, second, fortifying the financial system so that banks in developing countries can provide risk management products and advice to all economic agents, including small producers.